2016
DOI: 10.1007/s40259-016-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody and Fusion Protein Biosimilars Across Therapeutic Areas: A Systematic Review of Published Evidence

Abstract: BackgroundDespite regulatory efforts to formalize guidance policies on biosimilars, there remains a need to educate healthcare stakeholders on the acknowledged definition of biosimilarity and the data that underpin it.ObjectivesThe objectives of the study were to systematically collate published data for monoclonal antibodies and fusion protein biosimilars indicated for cancer, chronic inflammatory diseases, and other indications, and to explore differences in the type and weight (quantity and quality) of avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 182 publications
0
37
0
3
Order By: Relevance
“…2,16,44,57 A 2016 systematic literature review found that most comparative studies reported for such intended copies were either analytical, non-clinical, or observational in nature; as such, there remains a significant dearth of published data demonstrating the safety and efficacy of these agents. 16 …”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
See 4 more Smart Citations
“…2,16,44,57 A 2016 systematic literature review found that most comparative studies reported for such intended copies were either analytical, non-clinical, or observational in nature; as such, there remains a significant dearth of published data demonstrating the safety and efficacy of these agents. 16 …”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
“…These products (BCD-020, BEVZ92, and RTXM83) were considered “proposed biosimilars” in the aforementioned systematic literature review, and for each mAb there is evidence of one or more comparative clinical studies with the originator. 16,65 However, we have not identified detailed information in the public domain concerning the basis for regulatory approval in Latin America, and gaps have been highlighted in the published literature regarding these biologics. 16,65 Therefore, independent evaluation of these products is challenging.…”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
See 3 more Smart Citations